Analysis of the impact of global economy, society and energy development situation on power companies - Song Haixu (E3S Web of Conferences, 2021)
At present, the situation faced by power enterprises is becoming more and more complex, which has profound impact on the development of power companies. This article analyses the global development situation from three aspects: economic development, energy development, and technological development. In addition, it analyses the transformation trend of world-class energy and power companies such as EDF, E.ON, TEPCO and ENEL. On this basis, it proposes the development characteristics of power enterprises in the future, which provides reference for strategic analysis and optimization of power enterprises.